Design, synthesis and evaluation of XZH-5 analogues as STAT3 inhibitors. Issue 6 (15th March 2015) - Daka, Philias; Liu, Aiguo; Karunaratne, Chamini; Csatary, Erika; Williams, Cameron; Xiao, Hui; Lin, Jiayuh; Xu, Zhenghu; Page, Richard C.; Wang, Hong
Graphical abstract: Abstract: Inhibition of the signaling pathways of signal transducer and activator of transcription 3 (STAT 3) has shown to be a promising strategy to combat cancer. In this paper we report the design, synthesis and evaluation of a novel class of small molecule inhibitors, that is, XZH-5 and its analogues, as promising leads for further development of STAT3 inhibitors. Preliminary SARs was established for XZH-5 and its derivatives; and the binding modes were predicted by molecular docking. Lead compounds with IC50 as low as 6.5 μM in breast cancer cell lines and 7.6 μM in pancreatic cancer cell lines were identified.